A Field Guide to Deep-Sky Objects - Inglis, Mike. (The Patrick Moore Practical Astronomy Series,, 2012)
This popular title is now back, bigger and better than before! In this companion guide to stars, star systems, galaxies, and other deep sky sights you can choose a class of object and set up an annual program for yourself that will take you from month to month, helping you locate famous targets or, if you prefer, hunting down the lesser known but still dazzling sky sights. Detailed descriptive summaries of each class of object are followed by extensive lists of deep-sky targets, presented in a monthly format and going from those objects easy to locate to those that are more of a challenge. Amateur astronomers of all levels will find this book invaluable for its broad-ranging background material, for its comprehensive lists of fascinating objects, and for its power to improve your observing skills.